Mais que apenas pedras e pedradas : a produção de saúde em cenas abertas de uso de crack, pasta base de cocaína e similares - Abal, Yamila Soledad (2018)
Despite a progressive incorporation of a harm reduction approach in the Brazilian legislation, as well as in public policy about illegal drug use, a mostly prohibitionist approach, and its associated effects of repression and stigmatization, continues to produce conditions of infringement, causing greater damage than the substances themselves. Among some of the most profound consequences of this, are the enactment of barriers to access the health care system. Drawing on labeling theory, biopolitics and urban anthropology´s understandings of territoriality, this research used an ethnographic approach to investigate the production of health in open scenes of crack, cocaine base paste and other drugs use in the historic center of Cuiabá. To that end, we analyzed the kind of relationships that take place between the people who inhabit those territories, and the diverse types of institutionalized care dispositive, as well as selfcare mechanisms operating in these settings. We sought to identify to what extent, these relationships either reflect social control mechanisms, or if they constitute spaces of resistance – or if they are both instead. The findings of this research show that the open scenes of illegal drug use not only are crisscrossed by multiple and persistent forms of violence, but also, they are constituted as fields of health production, in which care practices based on intersubjective recognition and the construction of relationships of trust take place. Understanding these processes is important in order to produce information that is useful in the planification of interventions that deconstruct the barriers that limit access to the health care system to the groups who inhabit open scenes of crack, cocaine base paste and other drugs use.